Bioprospecting of tropical microalgae for high-value products: n-3 polyunsaturated fatty acids and carotenoids - Katayama, Tomoyo; Abdu Rahman, Norazira; Khatoon, Helena; Kasan, Nor Azman; Nagao, Norio; Yamada, Yuichiro; Takahashi, Kazutaka; Furuya, Ken; Abd Wahid, Mohd Effendy; Md. Yusoff, Fatimah; Jusoh, Malinna (Elsevier, 2022)
Microalgae are an important renewable source of carotenoids and polyunsaturated fatty acids (PUFAs), with strong antioxidant, anti-inflammatory, and hepatoprotective properties. In this study, indigenous microalgal strains from fresh, brackish, and marine waters of Peninsular Malaysia were isolated, purified, and cultured. The potential of microalgae as a natural source of lipids and carotenoids was studied using a screening test with Nile red fluorescence dye to examine the lipid and carotenoid contents. Of 125 microalgae strains, nine strains isolated from marine and brackish water samples (Chaetoceros gracilis, Chlorella sp., C. sorokiniana, C. vulgaris, Tisochrysis lutea, Nitzschia capitellata, Oocystella heteromucosa, Oocystis marina, and Thalassiosira weissflogii) showed high fluorescence intensities. Next, the biochemical composition of these nine strains was examined. Thalassiosira weissflogii (strain TRG10-p105) showed the highest production of n-3 PUFAs and carotenoids among the nine strains. This strain produced high levels of n-3 PUFAs, particularly eicosapentaenoic acid (EPA). In this strain, the EPA contents relative to the dry weight (DW) and total fatty acid content (10.8% and 21.4%, respectively) were considerably higher than those reported in species currently used in industrial applications, such as aquaculture. Thalassiosira weissflogii TRG10-p105 had the highest total carotenoid content (20.2 mg g−1 DW), primarily because of its high fucoxanthin content (11.5 mg g−1 DW). The findings of this study indicate that T. weissflogii TRG10-p105 can serve as a high-value microalgal strain from tropical regions that produces n-3 PUFAs and carotenoids in abundance. Because a high ammonium tolerance was observed in this strain, its large-scale production can be implemented in ammonium-rich water produced from waste products to reduce the cost of algae production.